1981
DOI: 10.1128/aac.20.4.481
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of piperacillin with observations on penetrability into cerebrospinal fluid

Abstract: Piperacillin, a new semisynthetic penicillin, was evaluated for efficacy and safety in 26 patients, most of whom had pneumonia. Included were four patients with gram-negative meningitis in whom the penetration of piperacillin into cerebrospinal fluid was determined. Cure was achieved in 11 of 17 patients with pneumonia; another 4 were improved. One relapse and one failure occurred among nine patients with gram-negative pneumonia. Cure or improvement occurred in seven of nine patients with gram-negative infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 22 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…Lastly, after coadministration with tazobactam, the penetration of piperacillin into the CSF of infected rabbits was in the range found previously in humans and in experimental animals (8,20 (6,18,20), and Proteus mirabilis (aminoglycosides) (21). Similar to the findings of these studies, rapid bactericidal activity in the present study was found when the ratio of CSF drug concentrations to the MBC was higher than 1Ox the MBC.…”
Section: Methodsmentioning
confidence: 70%
“…Lastly, after coadministration with tazobactam, the penetration of piperacillin into the CSF of infected rabbits was in the range found previously in humans and in experimental animals (8,20 (6,18,20), and Proteus mirabilis (aminoglycosides) (21). Similar to the findings of these studies, rapid bactericidal activity in the present study was found when the ratio of CSF drug concentrations to the MBC was higher than 1Ox the MBC.…”
Section: Methodsmentioning
confidence: 70%
“…Since oxacillin is ÏŸ90% protein bound, it is unlikely that trough-free drug levels of 32 g/ml (as used in this study) could be achieved in a clinical setting. However, depending on renal clearance, levels of ampicillin and piperacillin in blood of 75 to 80 g/ml (with proportional concentrations of sulbactam and tazobactam) are achievable with high-dose continuous infusions (4,6,9), and levels of ampicillin as high as 103 to 130 g/ml have been reported (11). Protein binding levels are reported to be 18% for both ampicillin and amoxicillin (7), 16% for piperacillin (2), 38% for sulbactam (3), and 20 to 23% for tazobactam (2).…”
Section: Discussionmentioning
confidence: 99%
“…Piperacillin has been shown to be effective in experimental and human Pseudomonas aeruginosa, Escherichia coli, and Streptococcus sp. meningitis (4,25). The combination of piperacillin and tazobactam was as potent as ceftriaxone in meningitis caused by a ␀-lactamase-producing E. coli strain (10).…”
mentioning
confidence: 99%